2013
DOI: 10.5414/cn108038
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hospitalizations in severe, refractory congestive heart failure with peritoneal dialysis: A consecutive case series

Abstract: Objective criteriabased institution of PD for the treatment of diuretic refractory severe-end-stage HF was well tolerated and demonstrated favorable outcomes; these included improved clinical status, reduced hospitalizations and length of stay, with very few and easily treatable PDrelated complications. PD appears to be a viable option in refractory, end-stage congestive heart failure (CHF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 0 publications
3
30
2
1
Order By: Relevance
“…This may lead to the restoration of responsiveness to diuretics [43]. However, we did not find any significant differences in diuretic dose before and after PD [9,24,44,45,46]. …”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…This may lead to the restoration of responsiveness to diuretics [43]. However, we did not find any significant differences in diuretic dose before and after PD [9,24,44,45,46]. …”
Section: Discussioncontrasting
confidence: 40%
“…Most recently, PD has been supported by several publications as another therapy for ultrafiltration in RCHF patients [7,8,9,10]. In 1951, the use of PD for RCHF was reported by Benhamou et al [11].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Theoretical advantages in favor of the use of PD rather than any form of intermittent or continuous hemodialysis are its gentle continuous ultrafiltration (avoiding neurohormonal pathway activation), being a permanent outlet from the abdominal cavity (thus keeping intra-abdominal pressure and venous congestion at their lowest), removing sodium efficiently, improving potassium levels (hence allowing [increased] use of renin-angiotensinaldosterone system blockers) and offering these benefits at home. Retrospective studies evaluating clinical effects of PD in patients with CRS2 showed significant reduction in number and duration of hospitalizations after initiation of PD, [54][55][56] improved functional New York Heart Association classification, 54,56,57 and improvement in left ventricular ejection fraction 54,55 at an acceptable cost of PD-related morbidity. [55][56][57] Continuous ambulatory PD (CAPD) was the main PD modality in these studies, all limited by the absence of a comparator group treated with an alternative renal replacement modality.…”
Section: Peritoneal Dialysis-related Peritonitismentioning
confidence: 99%
“…Retrospective studies showed improved functional NYHA classification for patients with refractory congestive heart failure treated with peritoneal dialysis [41,47] . The prospective study by Cnossen et al evaluating the effect of renal replacement therapy, PD or HD, on functional status confirmed a significant improvement in the NYHA class, both at 4 and 8 months after the start of dialysis [45] .…”
Section: Outcomes On the Functional Statusmentioning
confidence: 99%